2022
DOI: 10.3389/fphar.2022.808576
|View full text |Cite
|
Sign up to set email alerts
|

Kinsenoside Protects Against Radiation-Induced Liver Fibrosis via Downregulating Connective Tissue Growth Factor Through TGF-β1 Signaling

Abstract: Radiation-induced liver fibrosis (RILF) is a serious complication of the radiotherapy of liver cancer, which lacks effective prevention and treatment measures. Kinsenoside (KD) is a monomeric glycoside isolated from Anoectochilus roxburghii, which has been reported to show protective effect on the early progression of liver fibrosis. However, the role of KD in affecting RILF remains unknown. Here, we found that KD alleviated RILF via downregulating connective tissue growth factor (CTGF) through TGF-β1 signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…The common motif of m 6 A in LX2 cells was GGACUU (Figure S1D). Compared with the control group, there were less unique m 6 A peaks (10 523 vs. 11 547) and less genes with unique modification peaks (9581 vs. 10 261) in ALKBH5 knockdown group (Figure S1E). There were 3549 differential m 6 A peaks (fold change ≥ 2, p < .05) and 485 differentially expressed genes (fold change ≥ 2, p < .05) in ALKBH5 knockdown group, and 56 genes that showed differences in m 6 A peaks and gene expression were obtained by integrated analysis.…”
Section: Alkbh5 Promotes Ir-hsc Activation and Mediates Tirap Mrna M ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The common motif of m 6 A in LX2 cells was GGACUU (Figure S1D). Compared with the control group, there were less unique m 6 A peaks (10 523 vs. 11 547) and less genes with unique modification peaks (9581 vs. 10 261) in ALKBH5 knockdown group (Figure S1E). There were 3549 differential m 6 A peaks (fold change ≥ 2, p < .05) and 485 differentially expressed genes (fold change ≥ 2, p < .05) in ALKBH5 knockdown group, and 56 genes that showed differences in m 6 A peaks and gene expression were obtained by integrated analysis.…”
Section: Alkbh5 Promotes Ir-hsc Activation and Mediates Tirap Mrna M ...mentioning
confidence: 99%
“… 5 Hepatic stellate cell (HSC) is the key effector cell in the process of RILF. 6 Radiation‐induced HSC activation is a complex process involving a variety of cytokines and pathways. Our previous studies reported that radiation induces HSC proliferation and activation through nuclear factor‐kappa B (NF‐κB) and c‐Jun N‐terminal kinase (JNK)/Smad2 pathways, which promotes RILF development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the liver damage, HSCs in a resting condition are stimulated by fibrogenic mediators such as cytokines and are transformed to activated myofibroblasts, which produce and secrete excessive fibrosis-related proteins such as collagen and fibronectin to the perisinusoidal space, thereby leading to distortion of tissue structure and hepatic dysfunction ( Wu et al, 2007 ; Wu et al, 2010 ; Hsieh et al, 2011 ; Gao et al, 2021 ; Nie et al, 2022 ). Since a series of preclinical data have confirmed the positive roles of the inflammatory response and oxidative stress in exacerbating liver fibrosis, strategies impeding inflammatory cascades or relieving ROS burden display excellent anti-fibrotic abilities ( Binatti et al, 2022 ; Nassir, 2022 ).…”
Section: Potentials Of Kd Against Disease Developmentmentioning
confidence: 99%
“…Additionally, the switching of M1 macrophages to the M2 phenotype and inactivation of TLR4 signal pathway was implicated in the anti-fibrotic effects of KD. Interestingly, TGF-β1 was described as an inflammation-inhibiting factor and was up-regulated by KD in the model of autoimmune hepatitis, while it was reported that KD limited the expression of TGF-β1 to mitigate the development of fibrosis in the damaged liver ( Xiang et al, 2016 ; Nie et al, 2022 ). Several factors, including animal model type, inductive agent, stimulation dose and duration, and disorder stage might explain this paradox.…”
Section: Potentials Of Kd Against Disease Developmentmentioning
confidence: 99%